2008
DOI: 10.1088/1751-8113/41/27/275101
|View full text |Cite
|
Sign up to set email alerts
|

On the theory of cavities with point-like perturbations: part I. General theory

Abstract: Abstract. The theoretical interpretation of measurements of "wavefunctions" and spectra in electromagnetic cavities excited by antennas is considered. Assuming that the characteristic wavelength of the field inside the cavity is much larger than the radius of the antenna, we describe antennas as "pointlike perturbations". This approach strongly simplifies the problem reducing the whole information on the antenna to four effective constants. In the framework of this approach we overcame the divergency of series… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…A detailed derivation of the renormalized Green function can be found in Ref. 47. It is not clear how the coupling parameter Λ(E, R) depends on E or even on the LDoS.…”
Section: Local Density Of Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed derivation of the renormalized Green function can be found in Ref. 47. It is not clear how the coupling parameter Λ(E, R) depends on E or even on the LDoS.…”
Section: Local Density Of Statesmentioning
confidence: 99%
“…With the methods developed in Ref. 47, it is possible to derive an approximative description of the coupling for small cylindrical antennas showing an almost frequency independent prefactor Λ(E, R). Hence we finally obtain the relation between the LDoS and the reflection that is given by…”
Section: Local Density Of Statesmentioning
confidence: 99%
“…In Ref. 35 it was shown that for the correct analysis of transport one has to take into account the influence of coupling between the antennas and the waveguide. As a result, the Green's function for the empty waveguide in the normal-mode representation reads…”
Section: Experimental Setup and Basic Equationsmentioning
confidence: 99%
“…(9) may be used to estimate the resonance frequencies, this formula does not consider the effect of leading to a shift of resonances. It has been found [21] that the influence of surrounding noise or internal perturbation can cause a shift of resonances. Nevertheless, the next verification reveals that Eq.…”
Section: Distinction Between Resonant Modes and Eigenmodesmentioning
confidence: 99%
“…Moreover, numerous results of research [18][19][20] also reveal that external parameters such as the driven source and measuring device can cause the resonant modes to display various eigenmode-mixing phenomena. Scattering theory [21,22] has been used to study the frequency spectra and spatial patterns in microwave cavities because the entering and measuring antennas take the role of the scattering channels. However, for other experimental systems such as laser resonators and vibrating plates, the spatial patterns of resonant modes can be measured with the straightforward imaging method instead of the invasive scattering process.…”
Section: Introductionmentioning
confidence: 99%